Synthesis and antitumor activity of 1,3,4-oxadiazole substituted 2-(5-ylidene-2,4-dioxothiazolidin-3-yl)-acetamides - Maryan Lelyukh; Myroslava Kalytovska; Marta Zastryzhna; Arkadii Savchenko; Ihor Chaban; Stefan Harkov (Pensoft Publishers, 2023)
A series of novel 1,3,4-oxadiazole substituted 2-(5-aryl/heterylidene-2,4-dioxothiazolidine-3-ylidene)-acetamides and their 5-unsubstituted analogues have been synthesized following N-alkylation reaction of 2-chloro-N-(5-aryl-[1,3,4]oxadiazol-2-yl)-acetamides with thiazolidinedione and potassium salts of its arylidene derivatives. The structures of target compounds were confirmed by using 1H NMR spectroscopy and elemental analysis. Evaluation of anticancer activity in vitro for the synthesized compounds was performed in accordance with the National Cancer Institute protocol. A selective influence of some tested compounds against leukaemia MOLT-4 (3e, GP = 76.85%) and K-562 (3e, GP = 79.84%), colon cancer HCT-15 (3d, GP = 76.86%), renal cancer A498 (4a, GP = 74.37%), CAKI-1 (3d, GP = 68.49%) and UO-31 (3b-e, 4a-b, GP = 66.67 ÷ 86.30%) cell lines was established. Grafical abstract: